Treatment and Complications of Patients With Ipsilateral Acetabular and Femur Fractures: A Multicenter Retrospective Analysis. Issue 12 (December 2017) - Cannada, Lisa K.; Hire, Justin M.; Boyer, Preston J.; Israel, Heidi; Mir, Hassan; Halvorson, Jason; Della Rocca, Gregory J.; Ming, Bryan; Mullis, Brian; Deshpande, Chetan
Abstract : Objectives: The purpose of this study was to review the treatment of patients with ipsilateral acetabular and femur fractures to provide descriptive demographic data, injury pattern classification, treatment, and evaluate the complication profile reflective of current practices. Study Design: Multicenter retrospective cohort. Setting: Eight Level 1 Trauma Centers. Patients/Participants: One hundred one patients met inclusion criteria. Intervention: Surgical treatment of both the acetabular and femur fractures. Main Outcome Measurements: The complications evaluated include avascular necrosis, heterotopic ossification, posttraumatic arthritis, deep venous thrombosis, pulmonary embolism and superficial/deep infection, fracture union, and secondary surgeries. Results: Forty-three patients had 31 type fractures (29A; 11B, and 3C), 60 had 32 type (37A, 8B; 15C), and 8 had 33 type (1A, 4B, 3C) femur fractures; 10 patients had combinations involving more than 1 femur fracture pattern. There were 35 62A type fractures, 47 62B, and 19 62C acetabular fractures. Age of 45 or older was associated with marginal impaction ( P = 0.001). The aggregate infection rate was 17%. More than 30% of patients required secondary surgeries. The rate of avascular necrosis was higher in acetabular fractures combined with proximal femur fractures ( P < 0.05). The rate of deep venous thrombosis was associated with increased age and time to surgical fixation ( P < 0.05). Conclusions: We report the largest review of the surgical treatment and complications of ipsilateral acetabular and femoral fractures. This study provides useful information regarding the complications and provides some treatment recommendations regarding these injuries. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.